ANALISA KINERJA PENGEMBANGAN DESAIN POSISI RUANG BAKAR MIKROTURBIN GAS - Eko Prasetyo; Rudi Hermawan; Erlanda Augupta Pane (Fakultas Teknik Universitas Muhammadiyah Jakarta, 2022)
This research was conducted to develop a gas microturbine design by optimizing the position of the combustion chamber, which changes the position of the combustion chamber from vertical to horizontal and in a single axis with compressor and turbine components. The research method used is to calculate the change in the position of the combustion chamber from a vertical to a horizontal position, and thermodynamic analysis using the Brayton cycle in both ideal and actual conditions. The results of this research can be explained that the new design produces an outlet temperature of the combustion chamber or a gas turbine inlet temperature of 1242 K and a gas turbine outlet temperature of 870 K. This condition results in a thermal efficiency of 27.35%. Changing the position of the combustion chamber to a horizontal position in the development of gas microturbine designs can be concluded that can improve the performance of gas microturbine designs.